Perancangan Video Explainer Trans Jatim Menggunakan Power Point - Stevan Deyo Febrian; Bayu Setiawan (Student Research Journal, 2023)
This research aims to develop an explanatory video discussing the Trans Jawa Timur transportation system using Power Point software. The design approach includes combining visual, text and animation elements in Power Point to convey clear and interesting information about the East Java Trans. The author hopes that this explanatory video can be an effective communication tool to present and understand to the public the advantages and benefits of the Trans Jatim transportation system. It is hoped that the results of this research will provide guidelines for developing interactive and informative PowerPoint presentations for similar projects in the future.